Política y cultura: Biblioteca Contemporánea y Colección Austral, dos modelos de difusión cultural - Fernando Larraz (Orbis Tertius, 2008)
The beginning of the most successful period in Argentinaïs history of publishing, between 1937 and 1951, coincides with the launch of two pocket-book collections which were highly relevant for the education of one generation: the Biblioteca Contemporánea, by Losada; and the Colección Austral, by Espasa-Calpe Argentina. Both collections respond to publishing projects whose foundations are analyzed in this article. In order to do that, their origin is explained and an in-depth analysis of their catalogues between 1938 and 1945 is undertaken